2017
DOI: 10.1080/00380768.2017.1340813
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the relative importance of soil moisture, nitrogen, and temperature on the urea hydrolysis rate

Abstract: Urea hydrolysis is a complicated process influenced by multiple factors. Most previous studies only examined the causative factors of the process without ranking these factors' relative importance quantitatively. In this work, the experimental analysis method, ANOVA method, and backpropagation (BP) neural network method were used to rank the effects of moisture content (W), nitrogen amount (F), and temperature (T) on the urea hydrolysis rate. A group of 22 artificial neural network structures with different nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(53 reference statements)
0
4
1
Order By: Relevance
“…However, Sun et al (2017) found that the peak values of NH + 4 − N concentrations were delayed approximately 20 days after fertilizer application due to irrigation after fertilizer application. Others have found that high soil moisture limits urease activity (Du et al, 2007) and decreases the urea hydrolysis rate (Lei et al, 2017), which may have contributed to the differences seen in our study. An incubation experiment showed that the NH + 4 − N concentration reached its peak in the first week , which was similar to the results of this study.…”
Section: Spatial and Temporal Heterogeneity Of N Retention In The Soi...contrasting
confidence: 50%
“…However, Sun et al (2017) found that the peak values of NH + 4 − N concentrations were delayed approximately 20 days after fertilizer application due to irrigation after fertilizer application. Others have found that high soil moisture limits urease activity (Du et al, 2007) and decreases the urea hydrolysis rate (Lei et al, 2017), which may have contributed to the differences seen in our study. An incubation experiment showed that the NH + 4 − N concentration reached its peak in the first week , which was similar to the results of this study.…”
Section: Spatial and Temporal Heterogeneity Of N Retention In The Soi...contrasting
confidence: 50%
“…This is consistent with similar studies for urea applied to soil as granules (Lasisi & Akinremi, 2020; MacLean & McRae, 1987) or in solution (Moawad et al., 1984). However, a direct comparison of the rate of urea hydrolysis with past research is difficult as it is dependent on various factors such as the concentration of urea applied, soil temperature, soil moisture, and soil type (Broadbent et al., 1958; Lei et al., 2017), and for this sandy soil with low soil carbon and presumably low microbial biomass, urease capacity would be relatively low and/or the localized high concentration of ammonium near the fertilizer granule may have inhibited the rate of ammonification. The conversion of urea‐N, applied at a rate of 285 mg urea‐N kg −1 (Figure 3D) to NO 3 − was only ∼60% complete by 30 days for the sandy soil, with the remainder present as NH 4 + (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…As soil saturation increases, ammonia volatilization of synthetic N fertilizers can either be increased because of the faster hydrolysis process or decreased due to dilution in the soil solution. Moreover, high temperature encourages the hydrolysis process of synthetic N fertilizers and the rate of NH 3 diffusion from soil solution to the ambient environment ( Lei et al, 2017 ).…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%